Penerapan E-Commerce untuk Pemasaran Pertanian: Evaluasi Usability, Pengalaman Pengguna, dan Dampak Positif "Gawosa Shop" - Mahendra, Christy; Lianawati, Yosita; Wicaksono, Wilibrodus Megandika; Wijaya, Jonathan Briant; Santosa, Agnes Florentina; Kinanti, Maria Putri (Prosiding Seminar Nasional Teknoka, 2025)
Farmers in Gumiwang Village face significant challenges in marketing their harvests. To address this issue, the "Gawosa Shop" e-commerce platform was developed. This study evaluates the platform's usability, user experience (UX), and its impact on sales. Interface testing using the System Usability Scale (SUS) yielded an average score of 83.92, which is categorized as "Excellent." User Experience Questionnaire (UEQ) testing, which assessed six components (Attractiveness, Perspicuity, Efficiency, Dependability, Stimulation, and Novelty), showed results ranging from Good to Excellent. During the implementation period from October 1 to November 5, 2025, Gawosa Shop successfully increased revenue by 21.2% and the total number of orders by 116.7%. These findings indicate that Gawosa Shop is effective, well-received by its users, and provides a positive economic impact for the farmers in Gumiwang Village.